DESIGN OF A TACTICAL UNMANNED AIR VEHICLE (TUAV) WING STRUCTURE CONCERNING STATIC, BUCKLING, AND AEROELASTIC CONSTRAINT - Akmal Ramadhan, Faisal
The significant advancements in Tactical Unmanned Aerial Vehicle (TUAV) development have prompted Indonesian Air Force's Research and Development Agency (Dislitbangau) to conduct in-depth research on TUAV for military applications. The research object chosen by Dislitbangau is a Medium Altitude Long Endurance (MALE) TUAV, which is well-suited for surveillance and reconnaissance missions. In the present work, the structural design of a MALE TUAV wing is conducted. One of the TUAVs owned by Dislitbangau is used as the main reference of this work. The general configurations and the aicraft’s operating conditions are used as the basis of the design. A design process using the initial sizing approach is employed in this study. Once the structure is re-modeled through this process, the TUAV wing structure model is subjected to static and buckling loads to assess its strength under these conditions. The TUAV, however, is commonly designed with high aspect ratio wings. Thus, potential aeroelastic instability issues, i.e., divergence and flutter, should be evaluated carefully. In this research, the static and buckling loads analyses are conducted using the finite element method. The re-modeled wing structure depicts the static load’s safety factor of 6.25 and the critical buckling loads well above the total loads experienced by the wing. The dynamic characteristics in the form of natural frequencies and mode shapes are determined through structural dynamic analysis. The first five fundamental mode shapes are three bending modes, one swaying mode, and one torsional mode with natural frequencies between 8 to around 100 Hz. Furthermore, the dynamic aeroelastic analysis considering unsteady aerodynamic loads is performed using the Doublet Lattice Method (DLM) coupled with finite element method. Based on the aeroelastic instability analysis, within its operational speed range, the TUAV wing structure proves to be flutter-free and shows no signs of instability. This result is further verified through dynamic response analysis under sharp gust conditions during cruising. The response demonstrates rapid damping of vibrations at cruising speed, with the primary contributor being pure bending modes, without indications of influence from other vibration modes such as torsion that could lead to instability.